2020
DOI: 10.3389/fgene.2019.01390
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Immune-Related Prognostic Signature in Breast Cancer

Abstract: Background: Although increased early detection, diagnosis and treatment have improved the outcome of breast cancer patients, prognosis estimation still poses challenges due to the disease heterogeneity. Accumulating data indicated an evident correlation between tumor immune microenvironment and clinical outcomes. Objective: To construct an immune-related signature that can estimate disease prognosis and patient survival in breast cancer. Methods: Gene expression profiles and clinical data of breast cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
2
26
2
Order By: Relevance
“…By utilizing the breast cancer cohorts in the TCGA database and ESTIMATE algorithm-derived scores, we rst analyzed the relationship between stromal/immune scores and different stages or subtypes of breast cancer and found that stromal/immune scores were highly correlated with subtypes of breast cancer, especially in the basal-like subtype, and the luminal B and HER2-enriched subtypes also showed relevance with immune scores. This nding demonstrated that TME variation correlated with subtypes of breast cancer and possessed immunological characteristics, which is consistent with the ndings of a previous study [11]. However, the high immune-related scores did not predict a better prognosis in breast cancer subtypes.…”
Section: Discussionsupporting
confidence: 92%
“…By utilizing the breast cancer cohorts in the TCGA database and ESTIMATE algorithm-derived scores, we rst analyzed the relationship between stromal/immune scores and different stages or subtypes of breast cancer and found that stromal/immune scores were highly correlated with subtypes of breast cancer, especially in the basal-like subtype, and the luminal B and HER2-enriched subtypes also showed relevance with immune scores. This nding demonstrated that TME variation correlated with subtypes of breast cancer and possessed immunological characteristics, which is consistent with the ndings of a previous study [11]. However, the high immune-related scores did not predict a better prognosis in breast cancer subtypes.…”
Section: Discussionsupporting
confidence: 92%
“…Our ROC analysis showed that the AUC was 0.842 for 3-year OS and 0.808 for 5-year OS, higher than the AUC values reported in previous models (Lin et al, 2020;Xie et al, 2019), thus indicating that our model had better predictive ability.…”
Section: Discussioncontrasting
confidence: 75%
“…A 6-KIFs-based risk score (KIF10, KIF15, KIF18A, KIF18B, KIF20A, KIF4A) reported by Li et al [42] was proved to be associated with the prognosis in patients with breast cancer. Immune related index in breast cancer were also found through LASSO by Xie et al [43] and Zheng et al [44]. These researchers indicate that gene signatures could serve as risk factors for cancer management and played a vital role in predicting cancer prognosis.…”
Section: Discussionmentioning
confidence: 77%